2017
DOI: 10.7196/sajch.2017.v11i1.1148
|View full text |Cite
|
Sign up to set email alerts
|

Individual versus community-level measures of women decisionmaking involvement and child survival in Nigeria

Abstract: RESEARCHThis open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 16 publications
2
17
0
1
Order By: Relevance
“…It is possible that caregivers of higher educational level have higher knowledge on the importance of CWC. Thus, our finding is in consonance with previous studies which found education as an important predictor of parental health decision making for children [ 31 , 32 ]. This is so because caregivers with least formal education may have little or no knowledge on activities conducted at CWC after completion of the immunization schedule or may view such activities as irrelevant, as already established by other researchers [ 5 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is possible that caregivers of higher educational level have higher knowledge on the importance of CWC. Thus, our finding is in consonance with previous studies which found education as an important predictor of parental health decision making for children [ 31 , 32 ]. This is so because caregivers with least formal education may have little or no knowledge on activities conducted at CWC after completion of the immunization schedule or may view such activities as irrelevant, as already established by other researchers [ 5 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the data indicate the presence of unmeasured (omitted) variables operating at the cluster level that are associated with the use of bed nets. In this respect, this study echoes what prior studies have found in connection with malaria prevention [ 12 ] and other health areas [ 44 , 45 ]. While this study does not allow us to ascertain what these variables are, it is possible that they include factors related to community mobilization efforts, community engagement in malaria prevention efforts, housing density, and prevailing types of dwelling structures, such as the use or non-use of window netting.…”
Section: Discussionsupporting
confidence: 90%
“…This was done because the variables are not directly available in the DHS data. Most studies that have analysed community-level variables using DHS data adopted the method [ 28 , 29 , 48 ]. In addition, to the selected individual-level and community-level variables, three variables were selected for statistical control.…”
Section: Methodsmentioning
confidence: 99%